Pemanfaatan Limbah Agroindustri sebagai Bahan Baku Pangan Fungsional Berkelanjutan - Laila Hasanah; Ahmad Fauzi (Primary Journal of Multidisciplinary Research, 2026)
Agroindustrial waste is one of the major issues in the agricultural and food industry sectors, continuing to increase in line with the growth of agricultural production. Such waste is often underutilized, despite its significant potential as an alternative raw material source for the development of high-value functional foods. This study aims to examine the potential utilization of agroindustrial waste as a raw material in the development of sustainable functional food products and to assess its impacts on environmental, economic, and public health aspects. The method employed in this study is a comprehensive literature review encompassing the analysis of various previous studies related to different types of agroindustrial waste, such as fruit peels, agricultural residues, bran, and food processing by-products. The data were analyzed using a descriptive-qualitative approach to identify bioactive compounds, dietary fiber, antioxidants, and other functional components that can still be utilized in food formulations. In addition, this study discusses processing technologies that can enhance the value of such waste, including fermentation, extraction, and drying techniques. The findings indicate that agroindustrial waste has substantial potential as a raw material for functional foods. Its high dietary fiber content, phenolic compounds, and natural antioxidants make it suitable for processing into products such as functional flour, health beverages, high-fiber snacks, and dietary supplements. The utilization of this waste not only reduces negative environmental impacts but also provides additional economic value for agroindustrial stakeholders while promoting the diversification of healthy food products in society. Furthermore, the implementation of sustainability concepts in the utilization of agroindustrial waste can support the establishment of a more environmentally friendly and efficient food production system. However, several challenges remain, including limitations in industrial-scale processing technologies, food safety standards, and the low awareness among industry stakeholders regarding the potential value of agroindustrial waste. In conclusion, agroindustrial waste has very promising prospects as a sustainable functional food raw material, provided that it is supported by technological innovation, appropriate policies, and collaboration between industry and academia.